INSIGHTS INTO THE FUNCTIONAL POTENTIAL OF THE RICE WEEVIL ROSTRUM BASED ON MICROSTRUCTURE - S. Manivannan; S. Ezhilvendan (Journal of Animal and Plant Sciences, 2021)
The structural differentiation of rostrum in male and female adults of rice weevil, Sitophilus oryzae was examined under the light and electron microscopes to understand its functional potential in infestation/ovipositional tactics. The microscopic observation revealed that, the length of the rostrum was remarkably longer and thinner for females than in males. This adaptation in females is highly specific to deposit and protect eggs inside the grains. With the help of well-defined mouthparts in the apex of the rostrum, weevils chew and swallow food through the tunnel in the rostrum. No remarkable segments or sensillae were observed in both male and female rostrums. The study also signified that, rostrum could be used as a morphological marker key in differentiating males and females in S. oryzae and this species nearly shares common morphological features of rostrum with S. zeamais and S. granarius.
Keywords: Sitophilus oryzae; rice weevil; rostrum; insect pest; stored food products; SEM